2020
DOI: 10.1177/0091217420906979
|View full text |Cite
|
Sign up to set email alerts
|

Association of religiosity with mental health and quality of life in women with chronic pelvic pain

Abstract: Objective This study evaluated religiosity and its association with mental health, quality of life, and the intensity of pelvic pain in women with chronic pelvic pain. Methods A cross-sectional study was conducted with 100 women with chronic pelvic pain. Religiosity was investigated using the Duke University Religion Index. Quality of life was evaluated using the abbreviated version of the World Health Organization’s quality of life instrument. Depression and anxiety were assessed using the Hospital Anxiety an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…In the current study, we found no correlation between religiousness and pain incidence or intensity among PALS and controls from both countries (except for a weak positive correlation between total religiousness and frequency of pain in the German HCs). Similar results were obtained in North American and Brazilian patients with musculoskeletal [ 29 ] or pelvic pain, respectively [ 41 ].…”
Section: Discussionsupporting
confidence: 82%
“…In the current study, we found no correlation between religiousness and pain incidence or intensity among PALS and controls from both countries (except for a weak positive correlation between total religiousness and frequency of pain in the German HCs). Similar results were obtained in North American and Brazilian patients with musculoskeletal [ 29 ] or pelvic pain, respectively [ 41 ].…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, religiosity has been positively associated with quality of life in women with CPP. 90 Further studies are necessary to investigate psychological variables, 65 , 83 religiosity and spirituality 90 in women with CPP.…”
Section: Psychosocial Evaluationmentioning
confidence: 99%
“…Another option is to investigate, within the scope of the clinical interview, topics such as quality of life, sexual function, beliefs regarding pain, strategies for dealing with pain, family, social and religious support networks, and the impact of pain on an individual’s professional life. 8 , 65 , 66 , 90 The most important factor for a woman with CPP may be feeling that her complaints are being taken seriously and that she is being listened to, not necessarily through the use of previously validated instruments. Because CPP is a condition that requires long term monitoring, 99 more delicate subjects such as sexual function and a history of sexual abuse can be gradually addressed at future consultations when the relationship of trust between the healthcare professional and the patient has already been established.…”
Section: Psychosocial Evaluationmentioning
confidence: 99%